Heavy head lice infestation in an adolescent girl following benzodiazepine poisoning. Issue 2 (2nd February 2022) - Moghimi, Minoo; Nekoukar, Zahra; Sharifpour, Ali; Zakariaei, Zakaria; Fakhar, Mahdi; Soleymani, Mostafa
Abstract: Loss of consciousness (LOC) is one of the most common causes of emergency department (ED) visits. It may be due to intoxication or hypoglycemia. We present a 15‐year‐old girl who was referred with heavy head lice and LOC to the ED in the north of Iran. Abstract : Heavy head lice were detected on a 15‐year‐old girl who was admitted to the emergency ward with loss of consciousness and hypoglycemia following benzodiazepine poisoning.